2022
DOI: 10.32604/phyton.2022.020329
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Soil Respiration with An Elevation Gradient in Abies nephrolepis (Trautv.) Maxim. Forests in North China

Abstract: Soil respiration (Rs) plays an important role in regulating carbon cycle of terrestrial ecosystems and presents temporal and spatial heterogeneity. Abies nephrolepis is a tree species that prefers the cold and wet environment and is mainly distributed in Northeast Asia and East Asia. The Rs variations of Abies nephrolepis forests communities are generally environmental-sensitive and can effectively reflect the adaptive responses of forest ecosystems to climate change. In this study, the growing-seasonal variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Li et al [46] reported a significant linear regression relationship existed between soil temperature and soil respiration under both warming and control conditions, and their correlation was weaker under warming condition than control condition. Tian et al [47] showed that 76.9% and 25.8% of variation in soil respiration were controlled by soil temperature and soil water content alone in the Abies nephrolepis forest in Mount Wutai. In our study, soil temperature explained more variations of soil respiration under control condition than those under warming condition which indicted warming decreased the reliance of soil respiration on soil temperature.…”
Section: Regression Relationshipsmentioning
confidence: 99%
“…Li et al [46] reported a significant linear regression relationship existed between soil temperature and soil respiration under both warming and control conditions, and their correlation was weaker under warming condition than control condition. Tian et al [47] showed that 76.9% and 25.8% of variation in soil respiration were controlled by soil temperature and soil water content alone in the Abies nephrolepis forest in Mount Wutai. In our study, soil temperature explained more variations of soil respiration under control condition than those under warming condition which indicted warming decreased the reliance of soil respiration on soil temperature.…”
Section: Regression Relationshipsmentioning
confidence: 99%